Analisis Pengaruh Financing To Deposit Ratio, Rasio Efisiensi Kegiatan Operasional, Non Performing Financing, Dan Inflasi Terhadap Return On Asset pada Bank Umum Syariah di Indonesia Periode 2014-2019 - Siti Aminatun Jazila; Saniman Widodo; Siti Hasanah (Prodi Perbankan Syariah FAI UMT, 2021)
This study aims to analyze the significance effect of Financing to Deposit Ratio (FDR), Operasional Activity Efficiency Ratio (REO), Non Performing Financing (NPF) and Inflation toward Return On Asset (ROA) at Sharia Commercial Banks in Indonesia Period 2014-2019, both simultaneously and partially. The population in this study were all Sharia Commercial Banks in Indonesia period 2014-2019, while the sample in this study were 4 (four) Sharia Commercial Banks in the period of 2014-2019, which were selected using purposive sampling technique. The analysis model in this study is a multiple linear regression analysis model, and the analysis technique used the simultaneous test (F test), determination coefficient test (R2), and partial test (t test). The result of this study showed that the FDR, REO, NPF and Inflation simultaneously have a significant effect toward ROA at Sharia Commercial Banks in Indonesia period 2014-2019. Furthermore FDR partially has a positive but not significant effect toward ROA, REO partially has a negative and significant effect toward ROA, NPF partially has a negative but not significant effect toward ROA, and Inflation partially has a positive and significant toward ROA at Sharia Commercial Banks in Indonesia period 2014-2019.